2019
DOI: 10.1086/702198
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Factors That Influence Public Librarians’ Social Media Use for Marketing Purposes: An Adoption of the Technology Acceptance Model and Theory of Planned Behavior

Abstract: This study aims to explore multiple factors that are associated with social media use by public librarians for marketing purposes. Based on the technology acceptance model and theory of planned behavior, the effects of five factors-usefulness, ease of use, attitude, subjective norms, and behavioral control-on social media use intention were examined. A survey was conducted, and 462 valid responses were collected from public librarians across the United States. The findings revealed that all five factors have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 46 publications
5
10
0
1
Order By: Relevance
“…It can be seen from the empirical analysis in the previous section that ATT, SN and PBC have a significant positive impact on UI, consistent with the research conclusions of Joo et al (2019), of which ATT’s impact is the most significant. This shows that the “post-00s” (those born after 2000), college students in China are “a generation with attitude”.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…It can be seen from the empirical analysis in the previous section that ATT, SN and PBC have a significant positive impact on UI, consistent with the research conclusions of Joo et al (2019), of which ATT’s impact is the most significant. This shows that the “post-00s” (those born after 2000), college students in China are “a generation with attitude”.…”
Section: Discussionsupporting
confidence: 82%
“…The number of variables in these theories and models is limited, and it is necessary to integrate more related models in future studies (such as the information system success model) to dig out more significant variables. Given the difference in samples and application scenarios, this study’s conclusions are somewhat different from that of previous studies. For example, this study found that ATT has the most significant impact on UI, while Joo et al (2018, 2019) indicated that the effects of PBC are the most significant, and Heirman et al (2016) posited that the most crucial factor is the SN. Therefore, the generalization of this study’s results may present specific limitations.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations